Pengaruh Pertumbuhan Penjualan dan Kepemilikan Manajerial terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Pemoderasi - Siti Fitria Komala; Dea Annisa (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to examine and obtain empirical evidence regarding the effect of sales growth and managerial ownership on firm value, with firm size as a moderator, in infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the 2021 and 2023 periods. The research method used is quantitative with an associative approach. Secondary data obtained from company financial reports are used in this study. The sample was selected using a purposive sampling method with a population of sixty-nine companies. Twenty-five companies were sampled over a three-year period, resulting in seventy-five observations. The data analysis technique used was panel data regression analysis, with data processing using Eviews 12 software. The results of this study indicate that sales growth has no effect on firm value, managerial ownership does, firm size does not moderate the effect of sales growth on firm value, and firm size does not moderate the effect of managerial ownership on firm value. This study has several limitations, including the sample size which only covers one infrastructure sector over the three-year observation period and the limited number of independent variables used, as other factors can influence firm value. Furthermore, data collection is hampered by the failure of some companies to fully disclose their annual financial reports.